ANALYSIS OF DIGITAL MARKETING STRATEGIES IN INCREASING BRAND AWARENESS FOR RETAIL COMPANIES IN BANTEN - Susan Christiani (Institut Pendidikan Indonesia, 2025)
Digital marketing is becoming a crucial strategy for retail companies in increasing brand awareness amidst increasingly fierce market competition. By optimizing the use of social media, SEO (Search Engine Optimization), content marketing, and other digital platforms, retail companies can reach a wider audience at a relatively cost-effective price. This digital marketing strategy allows companies to increase brand visibility, build consumer engagement, and strengthen their market position. This method utilizes literature data collection, including journals, articles, books, and other reliable sources that discuss digital marketing strategies and brand awareness. The data is analyzed systematically and critically to gain an in-depth understanding of how digital marketing strategies can enhance brand awareness, particularly in the retail sector. This research analyzes the implementation of various digital marketing strategies by retail companies in Banten and their impact on increasing brand awareness. The results show that the use of social media, targeted digital advertising, and search engine optimization significantly contributes to increasing brand awareness, while also addressing challenges such as the rapid changes in digital trends and limited resources. In conclusion, a planned and adaptive digital marketing strategy is essential for increasing brand awareness and the competitiveness of retail companies in the Banten region